Optimalisasi Pengawasan Tempat Praktik Mandiri Dokter (TPMD) Dalam Pelayanan Estetika Untuk Menjamin Keselamatan Pasien - Diah Elvira Syafruddin; Jasrida Yunita; Hetty Ismainar; Oktavia Dewi; Emy Leonita; Dendi Zulheri (Jurnal Medika: Medika, 2026)
Medical aesthetic services in Indonesia, particularly in Pekanbaru City, have developed rapidly and require effective supervision to ensure service quality and patient safety. This community service activity aimed to improve the understanding and compliance of Independent Medical Practice Clinics (TPMD) in providing aesthetic services in accordance with healthcare standards and regulations. The implementation methods included socialization, education, mentoring, field observation, and discussions involving the Pekanbaru City Health Office, professional organizations, and physicians responsible for aesthetic TPMD. The activities were conducted using a participatory approach focusing on licensing, the use of approved medicines and medical devices, service standards, recording and reporting systems, and patient safety. The results showed that several challenges remain in the supervision of aesthetic TPMD, including limited human resources, inadequate facilities and infrastructure, and insufficient budget support. In addition, regulations related to aesthetic practice are still general in nature, while supervision activities tend to be administrative and incidental. TPMD understanding regarding aesthetic service standards and patient safety was also found to be suboptimal. Through this activity, participants demonstrated improved knowledge regarding safe and legal aesthetic practice standards and the importance of compliance with healthcare regulations. This community service activity is expected to strengthen collaboration among the Health Office, professional organizations, and TPMD in improving supervision effectiveness, service quality, and patient safety in medical aesthetic services in Pekanbaru City